The Effect of Informative Video to Reduce Anxiety in Patients with Third Molar Surgery - Nita Layli Hanifah; Eti Poncorini Pamungkasari; Rita Benya Adriani (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Dental anxiety is one type of anxiety that provides major complications for patients and dentists. Third molar extraction is one of the most common surgical procedures in the field of oral and maxillofacial surgery which is accompanied by various anxiety triggers. Anxiety due to procedures performed during dental procedures causes anxiety 60%-80% in patients who will undergo surgery. This study aims to estimate the effect of providing informative videos on the level of anxiety in patients undergoing third molar surgery based on a number of previous primary studies.Subjects and method: This study is a systematic and meta-analysis study, with the following PICO Population: Patients 18-45 years old old, Intervention: Informative video about third molar surgery, Comparison: Without informative video, Outcome: Anxiety levels. The articles used in this study were obtained from several databases, including PubMed, Scopus, Hindawi, Proquest, ScienceDirect and Google Scholar. This article was collected for 1 month. The keywords to search for articles were as follows: